Pulsed Radiofrequency Therapy in Eldeerly People with Trigeminal Neuralgia: A Case Report - Sulistyo Bambang; Laksono Ristiawan Muji (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Introduction: A face nerve disorder known as trigeminal neuralgia is regarded as one of the most excruciating human ailments. Depending on the patient's medical comorbidities, trigeminal ganglion interventional techniques can lessen discomfort. The application of brief radiofrequency pulses via a needle tip that do not result in genuine thermal lesions is known as Pulsed Radiofrequency (PRF) therapy. Case: Elderly man complained of pain in the right upper and lower jaw. He was diagnosed atypical trigeminal neuralgia. The man got pulsed radiofrequency on the right trigeminal nerve with the help of C-arm, with temperature specifications of 42o C, voltage 45V, pulse width   20 ms, frequency 2 Hz, with a duration of 8 minutes.  1 week after the procedure, the VAS became 0. Oral therapy still continued. Discussion: The most prevalent cranial neuropathy is trigeminal neuralgia (TM). Traditional RF for TM is not without its problems. Research indicates that both early and late alterations in cellular activity, unaffected by temperature, take place in the cervical dorsal root ganglion (DRG) and rat dorsal horn following PRF exposure. According to meta-analysis, PRF is safer and more effective than conventional radiofrequency. By decreasing phosphorylated extracellular signal regulated kinase (a central sensitization biomarker), decreasing Ca 2+ influx, which lowers nerve cell potential activity, and decreasing mitochondrial membrane potential, which lowers cytosolic ATP levels, PRF modifies sensory ganglion nerve cells. Reduced sensitivity to pain results from a decrease in nerve ganglion cell activity. Conclusion PRF for trigeminal neuralgia can be alternative treatment with better safety and efficacy.